Micro‐straw: An efficient cryopreservation carrier for rare human spermatozoa. (23rd February 2022) - Luo, Xue‐Feng; Huang, Chuan; Ji, Xi‐Ren; Luo, Qiang; Tang, Yu‐Lin; Zhou, Wen‐Jun; Huang, Zeng‐Hui; Liu, Qian; Fan, Li‐Qing; Zhu, Wen‐Bing
Abstract: Background: Many cryopreservation carriers have been introduced to freeze rare human spermatozoa, however, these carriers relative attributes and comparative effectivenesses have not yet been systematically studied. Objectives: Is the micro‐straw cryopreservation carrier more effective for cryopreserving rare human spermatozoa compared with the Cryoplus and a new micro‐straw (LSL straw) carriers? Materials and methods: This study involves 93 samples from healthy sperm donors and 40 samples from patients diagnosed with oligospermia, asthenospermia, oligoasthenospermia, or obstructive azoospermia. We determined the optimal freeze–thaw protocol for the Micro‐straw carrier. The post‐thaw survival rate, normal sperm morphology, acrosome integrity, and DNA fragmentation for Micro‐straw, Cryoplus, and LSL carriers were then determined. Finally, we verified the effects of freezing using these carriers by comparing the qualities of post‐thaw spermatozoa from patients. Results: The highest total motility (TM) and progressive motility (PR) survival rates were obtained by placing the Micro‐straw at 1 cm above the LN2 surface for 70 s during freezing and in a 42°C water bath for 40 s during thawing. No differences were observed in the PR survival rate, acrosome integrity, and DNA fragmentation of the post‐thaw spermatozoa from the three carriers. However, the normal morphology rate of spermatozoa frozen using the Micro‐straw carrier was higher than for the Cryoplus carrier ( p  < 0.05), and the TM survival rate of spermatozoa frozen with the Micro‐straw was higher than that for the LSL carrier ( p  < 0.01). In verification tests, there were no significant differences in the quality of post‐thaw spermatozoa cryopreserved using these carriers for both rare spermatozoa or epididymal sperm. Discussion and conclusion: Micro‐straw, Cryoplus, and LSL carriers are all efficient means of freezing rare human spermatozoa. However, the Micro‐straw carrier is more economical, safe, and user‐friendly.